Estilos de aprendizaje vak y su influencia en el rendimiento académico de los estudiantes de octavo a décimo año de educación básica de la Unidad Educativa Insutec, del Cantón Quevedo, Provincia de los Ríos, año 2015 - Criollo Vinza, Ruth Teresa (2015)
This research is performed in the Educational Unit Insutec, in order to analyze the influence of learning styles VAK in the academic performance of students from eighth to tenth year of basic education to reach the target a study was conducted on learning styles prevalent in students, and teachers analysis on the implementation of the methodology based on learning styles, to apply academic techniques to help improve academic performance. The methodology implemented based on the types of field research to analyze the real situation where the facts and explanatory to understand why the facts by establishing cause and effect, develop methods are statistical, inductive, fenomenológico for scope of the results. The results of the study at the Educational Unit Insutec students from eighth to tenth year of basic education, it was found that the predominant style is kinesthetic visual, followed by auditory visual kinesthetic, recommending that it is important to encourage students to use strategies taught by the teacher to improve its development of thought, a greater understanding and analysis achieving further develop their learning